2019
DOI: 10.1101/535419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term Brillouin imaging of live cells with reduced absorption-mediated damage at 660nm wavelength

Abstract: In Brillouin microscopy, absorption-induced photodamage of incident light is the primary limitation on signal-to-noise ratio in many practical scenarios. Here we show that 660 nm may represent an optimal wavelength for Brillouin microscopy as it offers minimal absorption-mediated photodamage at high Brillouin scattering efficiency and the possibility to use a pure and narrow laser line from solid-state lasing medium. We demonstrate that live cells are ~80 times less susceptible to the 660 nm incident light com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…To ensure that mechanical heterogeneities were not driving cell migration to the microwell edge via durotaxis (41,42), we mapped the local longitudinal moduli of the hydrogels using Brillouin microscopy (43,44). The Brillouin frequency shift is sensitive to changes in material stiffness and has previously been used to characterize several types of soft materials, including gelatin-based hydrogels (45).…”
Section: The Topography and Mechanical Properties Of The Hydrogel Microwells Are Uniformmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that mechanical heterogeneities were not driving cell migration to the microwell edge via durotaxis (41,42), we mapped the local longitudinal moduli of the hydrogels using Brillouin microscopy (43,44). The Brillouin frequency shift is sensitive to changes in material stiffness and has previously been used to characterize several types of soft materials, including gelatin-based hydrogels (45).…”
Section: The Topography and Mechanical Properties Of The Hydrogel Microwells Are Uniformmentioning
confidence: 99%
“…We measured the Brillouin shift of the hydrogels using a twostage Virtually Imaged Phase Array (VIPA) spectrometer as described previously (44,67). In brief, the sample was illuminated with 660 nm laser light through a 60x, 0.7NA objective (Olympus).…”
Section: Brillouin Microscopy Measurementsmentioning
confidence: 99%
“…However, it also decreases the signal intensity due to the inverse relationship with the forth power of incident wavelength (as well as reducing the frequency shift). Nikolic and Scarcelli [8] showed that the use of 660 nm wavelength enables live cells to be irradiated with 82 times more energy than at 532 nm, thus shortening the acquisition time (by ca. 34 times).…”
Section: Introductionmentioning
confidence: 99%